Antisense Oligonucleotide: Basic Concepts and Therapeutic Application in Inflammatory Bowel Disease - Di Fusco, Davide; Dinallo, Vincenzo; Marafini, Irene; Figliuzzi, Michele M.; Romano, Barbara; Monteleone, Giovanni (Frontiers in Pharmacology, 2019)
Several molecular technologies aimed at regulating gene expression that have been recently developed as a strategy to combat inflammatory and neoplastic diseases. Among these, antisense technology is a specific, rapid, and potentially high-throughput approach for inhibiting gene expression through recognition of cellular RNAs. Advances in the understanding of the molecular mechanisms that drive tissue damage in different inflammatory diseases, including Crohn’s disease (CD) and ulcerative colitis (UC), the two major inflammatory bowel diseases (IBDs) in humans, have facilitated the identification of novel druggable targets and offered interesting therapeutic perspectives for the treatment of patients. This short review provides a comprehensive understanding of the basic concepts underlying the mechanism of action of the oligonucleotide therapeutics, and summarizes the available pre-clinical and clinical data for oligonucleotide-based therapy in IBD.